Strategi Pengelolaan Kelas di SDN Gondangrejo - Ningsih, Mulati; Wijayanto, Sukma (Prosiding University Research Colloquium, 2021)
This study aims to explore teacher attitudes in maximizing class potential; class management inhibiting factors; teacher’s efforts in overcoming classroom management problems; and classroom management strategies. This case study was conducted at SDN Gondangrejo, and used a qualitative approach. The data from this study were obtained through interviews and observations regarding classroom management. The results of this study indicate that in classroom management the teacher functions as a counselor, facilitator, motivator, demonstrator, and evaluator. Therefore, teachers are able to analyze problems surrounding students, teachers, as well as the physical and socio- emotional environment in the classroom. Regarding this, teachers try to apply preventive and corrective. Teachers tend to use an eclectic approach, namely applying two or more approaches at the same time. Thus, it is hoped that the eclectic approach can assist teachers in improving the quality of choosing an approach that allows them to overcome problems regarding classroom management